Fashion in Amman new camp: An ethnographical study of consumption in a Palestinian refugee camp - Fortner-Dominguez, Ashley (AUC Knowledge Fountain, 2017)
This thesis is an ethnography conducted with the residents of the Amman New Camp (Wihdat) on their fashion consumption. Consumption is approached as a multidimensional structure that exhibits itself in common and uncommon ways of life and it also permeates people's conceptualizations of the world in which they live as well as the creation of their own identities. It therefore interacts with the fundamental elements of social life and culture, relaying a channel by which messages and meanings are exchanged or transferred. It spans over a wide range of practices and generates diverse styles for embedding people and societies into trends that sustain this structure. Consumption styles and trends that are embedded in this structure define much wider elements, both along hierarchies and along highly subjective preferences, all of which function to consolidate norms and ways of being across different domains of life. I explore the environment and lives of the Wihdat residents, living with them and participating in some of their daily and occasional consumption of fashionable commodities. Three main themes emerge to represent the core categories in which fashion consumerism occurs - consumption of homes, clothing, and bodies. The consumption that occurs in these categories is detailed by complex needs that come as signifiers for norms, desires, preferences, and values. Islamic values emerge for a variety of commodities consumed across the three categories but they interlace with a wide range of subjective individual and collective perceptions, all of which interact with the camp conditions and ways of life as has come to be established by the residents and the community at-large.